Active Aging From A Skipped Generation Family in a Rural Area to Urbanization: The Study Koh Kaew Subdistrict Municipality, Tha Muang Subdistrict Municipality, Selaphum District, Roi Et Province, Thailand - Muenthaisong, Chanajai; Weeranakin, Pattaraporn (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2021)
The objective of the research article were to study the active aging from a skipped generation family in a rural area to urbanization : the study Koh Kaew Subdistrict Municipality, Tha Muang Subdistrict Municipality, Selaphum District, Roi Et Province, Thailand. The researcher used qualitative research methodology. Data were collected by the use of in-depth interviews. An example used in the research was elderly people who came from skipped generation family age between 56-58 years old and aged between 67-73 years old. 11 people, data collected during January-April 2019, using content analysis. The results showed of the active aging from a skipped generation family in a rural area to urbanization: a study of Koh Kaew Subdistrict Municipality, Tha Muang Subdistrict Municipality, Selaphum District, Roi Et Province, Thailand : are as follows: 1) Participation: The elderly participation is through traditional activities, culture and Buddhism, elderly participation is also in elderly school activities in the community 2) Health: mental health, physical health 3) Conditions that are conducive to power: Using mobile phones, Watching television news ,Receiving information through community leaders 4) Creating job security for the elderly: Own farm, Own a residence, Extra careers off-season agriculture and participation in community business.